Functionality evaluation of co-processed excipients as diluents in tablets manufactured by wet granulation - Eshovo Apeji Y.; Muhammad IY; Kehinde Olowosulu A.; Owoicho Okpanachi G.; Rukayat Oyi A. (Sciendo, 2021)
Diluents are essential components of a tablet formulation. The type of diluent used in a formulation influences the quality of tablets produced from that formulation. The aim of this study was to evaluate the tableting properties of co-processed excipients (C-PEs) incorporated as diluents in tablet formulation by wet granulation. Metronidazole tablets were prepared by wet granulation incorporating different diluents that were either single component excipients (SCEs) (lactose and microcrystalline cellulose) or C-PEs (Ludipress®, StarLac®, Prosolv® and AVICEL®HFE). The granules obtained for each formulation were evaluated for particle size analysis, flow properties and compression properties. Tablets weighing 500 mg were compressed from the metronidazole granules on a Single Station Tablet Press using a 12 mm punch and die tooling system. The tablets were kept for 24 h post-production, and the properties of weight uniformity, thickness, tensile strength, friability, disintegration time and dissolution profile evaluated subsequently. Results of granule properties showed that variations in parameters evaluated was as a result of differences in the type and composition of diluent used in formulation. Compactibility and tabletability profile of metronidazole granules revealed a better performance with granules processed with C-PE based diluents compared to SCE-based diluents. Tablets formulated with C-PEs as diluents were uniform in tablet weight, disintegrated faster and yielded a faster drug release compared to tablet formulations containing SCEs as diluent. This study reveals the performance advantage of C-PEs as diluents in tablets manufactured by wet granulation and highlights the importance of rational selection of excipients during tablet formulation.